2023
DOI: 10.3389/fendo.2023.1158153
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter-2 inhibitors use and the risk of gout: a systematic review and meta-analysis

Abstract: ObjectiveTo assess the relationship between use of sodium-glucose cotransporter-2 inhibitors (SGLT2i) and the risk of gout among patients with type 2 diabetes mellitus (T2DM).MethodsA systemic review and meta-analysis were designed by reviewing articles published between 2000 January 1 and 2022 December 31 using PubMed system and Web of Science system based on the PRISMA 2020 guidelines. The end point of interest was gout (including gout flares, gout events, starting uric-acid lowering therapy and starting ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…By preventing reabsorption, SGLT2i can increase the concentration of glucose reaching the collecting ducts, which in turn compete with urate for reabsorption via the GLUT9 isoform 2 leading to the excretion of more uric acid. Other mechanisms involving activation of the xanthine oxidase by sirtuin activation and alteration of URAT1 transporter have been also proposed[ 32 ]. In a nationwide study from Taiwan, that investigated the association, the use of SGLT2i was associated with a lower incidence of gout (HR: 0.89; 95%CI: 0.82-0.96) than DPP4 inhibitors, and this was particularly seen in patients receiving dapagliflozin[ 33 ].…”
Section: Effects Of Sglt2i On Different CV Risk Factorsmentioning
confidence: 99%
“…By preventing reabsorption, SGLT2i can increase the concentration of glucose reaching the collecting ducts, which in turn compete with urate for reabsorption via the GLUT9 isoform 2 leading to the excretion of more uric acid. Other mechanisms involving activation of the xanthine oxidase by sirtuin activation and alteration of URAT1 transporter have been also proposed[ 32 ]. In a nationwide study from Taiwan, that investigated the association, the use of SGLT2i was associated with a lower incidence of gout (HR: 0.89; 95%CI: 0.82-0.96) than DPP4 inhibitors, and this was particularly seen in patients receiving dapagliflozin[ 33 ].…”
Section: Effects Of Sglt2i On Different CV Risk Factorsmentioning
confidence: 99%
“…Notably, there is growing evidence of the potential benefits of SGLT-2 inhibitors for lowering serum uric acid levels 18 19. A recent meta-analysis showed that in patients with diabetes mellitus, the risk of gout was reduced in those using SGLT-2 inhibitors compared with those not using SGLT-2 inhibitors (HR 0.66, 95% CI 0.57 to 0.76) 20. However, there is no comparison of the effects of different SGLT-2 inhibitors on serum uric acid levels in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%